Evaluation of the Heart Function of Swimmers Subjected to Exhaustive Repetitive Endurance Efforts During a 500-km Relay - Gajda, Robert; Kowalik, Ewa; Rybka, Sławomir; Rębowska, Ewa; Śmigielski, Witold; Nowak, Michał; Kwaśniewska, Magdalena; Hoffman, Piotr; Drygas, Wojciech (Frontiers in Physiology, 2019)
Aim: Knowledge of the human body’s ability to adapt to repeated endurance efforts during swimming is limited. We echocardiographically assessed the impact of an exhausting and repetitive swimming effort on cardiac activity. Materials: Fourteen well-trained amateur swimmers (8 female swimmers aged 16-43 years and 6 male swimmers aged 13-67 years old) participated in an ultramarathon relay. Over 5 days, swimmers swam 500 km in the Warta River (in 5-km intervals). Each swimmer swam seven intervals, each within 44:46 to 60:02 minutes. Objective difficulties included low water temperatures, strong winds, rain, and night conditions. Methods: Transthoracic echocardiography (TTE) was performed three times: at baseline (the day before exertion), at peak effort, and during recovery (48 hours after the event). The heart rate (HR) of each swimmer was monitored. Results: Swimmers completed the ultramarathon relay within approximately 91 hours. The average HR value at the end of each interval was 91% HRmax. TTE test results showed no significant changes indicative of deterioration of myocardial function at peak effort or after 48 hours. Significant increases in left ventricular (LV) ejection fraction, LV fractional shortening (LVFS), LV myocardial systolic velocity, and right ventricular (RV) fractional area changes observed on day 2 after swimming were compared to baseline values and peak effort values. No significant changes in diastolic heart function were observed. Conclusions: Echocardiography assessment indicated that prolonged intense swimming does not affect LV or RV function. Supercompensation of the post-event RV function and increased global LV systolic function demonstrated ventricular interaction after prolonged intense swimming.